Perbandingan kompetensi literal dan apresiatif siswa kelas iv sd dalam memahami isi teks fiksi - 'Azizah, Naeliyatun; Karsono, Karsono; Kamsiyati, Siti (Didaktika Dwija Indria, 2023)
Abstract. Understanding the content of reading text is one of the language skills included in reading skills. This study aims to describe the ability of fourth grade students in understanding the contents of fictional texts in terms of Barrett's taxonomy theory, developed by focusing on literal comprehension and appreciation comprehension. This research is a descriptive qualitative research. The subjects in this study were fourth grade students and fourth grade teachers at Soropadan Elementary School. The data collection used in this research was observation, tests, interviews with fourth grade students and fourth grade teachers, and document studies. The data analysis technique in this study used the interactive data analysis technique of the Miles and Huberman model. Data validity testing technique uses source and technique triangulation. The results of this study show that the percentage obtained on the literal understanding comprehension is 91.35% and 35.79% on the appreciation comprehension. The results of the study show that students perform better in literal comprehension than in appreciation comprehension.